ASSESSMENT OF MAIZE GRAIN QUALITY BY DNA MARKERS - Prysiazhniuk L. M.; Honcharov Yu. O.; Shytikova Yu. V.; Melnyk S. I. (Scientific Journal of Pedagogy and Economics, 2021)
To evaluate maize lines on the basis of the high content of lysine and tryptophan and waxiness using SSR markers.